Kontribusi Pendidikan Agama Islam terhadap Kesehatan Mental - Afifah, Juliana Nur; Lukman, Zahra Asyifa; Indriyanti, Andini; Anwar, Saepul (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2024)
Many teenagers have mental health problems, and many studies state that religiosity contributes to a person's mental health. The research aims to find out whether Islamic religious education contributes to adolescent mental health. In this research, researchers used mixed research methods using convergent design. Researchers used the Mental Health Continuum-Short Form and the Understanding of Islamic Religious Education measuring instruments for quantitative research. Respondents who participated in this research were Muslim teenagers aged 15-20 years who were active pupils and students from several educational institutions in Indonesia. Researchers used descriptive data analysis techniques. The regression test results show that Islamic religious education has an influence of 8.1% on adolescent health, while other factors influence 91.9%. The quantitative results in this research are strengthened by the views of the head of the West Java MUI fatwa, the West Java PWNU expert council, and psychology lecturers at the Indonesian Education University. From the results of interviews with these three figures, a conclusion can be drawn that Islamic religious education has a contribution to the mental health of teenagers.